Corporatization in local government: Promoting cultural differentiation and hybridity?. (4th May 2021) - Berge, Dag Magne; Torsteinsen, Harald
Abstract: Corporatization implies disintegration of public authority, leading to not only structural but also cultural differentiation of government, transforming it into a fragmented and hybrid governance system consisting of an authority and multiple autonomous or semi‐autonomous operators. This article addresses corporatization at the local government level in Norway, exploring if and how this change in formal structure triggers the emergence of separate cultures in the operator entities. Described as an institutionalization process, new norms, cognitions and identities seem to develop in these entities, creating a sense of 'us' (the municipal company) and 'them' (the municipality), thus strengthening the regulative separateness through normative and cultural‐cognitive elements. Findings from our multiple‐case study indicate that this process may be relatively fast and strong, transforming local government into a system comprising various hybrid types, especially segregated and assimilated types. The stronger the structural differentiation is, the stronger cultural differentiation seems to be.